2013
DOI: 10.1182/blood-2012-08-449140
|View full text |Cite
|
Sign up to set email alerts
|

MAPK pathway activation leads to Bim loss and histone deacetylase inhibitor resistance: rationale to combine romidepsin with an MEK inhibitor

Abstract: Key Points MAPK pathway activation and Bim loss may represent a fundamental mechanism of resistance to histone deacetylase inhibitors. Combination of romidepsin with an MEK inhibitor may lead to greater responses in cancers in which the MAPK pathway is active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 37 publications
10
69
0
1
Order By: Relevance
“…11 We recently demonstrated that upregulation of the mitogen-activated protein kinase pathway led to Bim degradation and resistance to histone deacetylase inhibitors in a model of cutaneous T-cell lymphoma. 12 Combination of an HDI with inhibitors of signaling pathways leads to increased apopotosis in several cell line models. [13][14][15] Various reports have shown that HDIs mediate apoptosis through both the intrinsic and extrinsic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…11 We recently demonstrated that upregulation of the mitogen-activated protein kinase pathway led to Bim degradation and resistance to histone deacetylase inhibitors in a model of cutaneous T-cell lymphoma. 12 Combination of an HDI with inhibitors of signaling pathways leads to increased apopotosis in several cell line models. [13][14][15] Various reports have shown that HDIs mediate apoptosis through both the intrinsic and extrinsic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Romidepsin induced p21 in all 4 cell lines while belinostat induced p21 in THJ-21T and vorinostat induced p21 in THJ-11T and THJ-21T. Since BIM degradation can be regulated by Erk signaling (Akiyama, et al 2009; Chakraborty, et al 2013), p-Erk and p-Akt (data not shown) expression was examined and no consistent change in expression was found within or across the four ATC cell lines examined (Figure 1C). …”
Section: Resultsmentioning
confidence: 94%
“…The loss of the pro-apoptotic protein Bim and the abnormal activation of the mitogen-activated protein kinase pathway could be a fundamental resistance mechanism to HDACi compared with parental cells (19). Chakraborty et al (20) have therefore studied in vitro the combination of romidepsin, which is another HDACi, with an anti-mitogen-activated kinase (MEK) for the treatment of CTCL. In vitro, the anti-MEK combined with romidepsin leads specifically to apoptosis and could then be correlated with the restoration of Bim.…”
Section: Discussionmentioning
confidence: 99%